Factors Associated With Legal Decisions of Nonfatal Strangulation Cases With Forensic Evidence - Reckdenwald, Amy (Criminal justice policy review, 2024)
This study examines the influence of offender, victim, and case characteristics along with available forensic evidence on legal outcomes of nonfatal strangulation (NFS) cases. Research points to the importance of NFS forensic evidence collection to corroborate the attack during legal proceedings. However, little is known regarding the factors associated with legal decisions for NFS cases with forensic evidence. Law enforcement reports, forensic medical examinations, and legal outcomes for 63 NFS cases in Florida were analyzed. Findings have implications for the criminal justice system, as forensic medical exams can be used to collect valuable evidence to support prosecution outcomes.